Sentinel Lymph Node Detection in Breast Cancer – First Experience - Stojanoski, Sinisa; Ristevska, Nevena; Pop Gjorcheva, Daniela; Antevski, Borce; Petrushevska, Gordana (Macedonian Academy of Sciences and Arts / Walter de Gruyter GmbH, 2015)
Abstract Introduction: Breast cancer accouns for 22.9% of all cancers in women and 13.7% of cancer deaths. Positive axillary lymphnodes (ALN) predict the development of distant metastases. The status of the sentinel lymphnode (SLN) is crutial for the treatment selection. Aim: To determine the benefits of SLN detection in patients with breast cancer. Material and methodology: 38 female patients (pts), age 44 ± 12 years, with T1-2 N0 M0 breast cancer, without enlarged ALN on ultrasound (US), were included. SLN detection was performed using gamma camera and gamma detection probe after periareolar subcutaneous and/or peritumoral injection of (99m-Technetium-SENTISCINT). Blue dye was administered 20 min before the operation. SLN was extirpated and ex tempore histopathology was performed. Results: Ex tempore SLN evaluation was negative and the lymphatic pathways preserved in 28/38 (74%) pts. In 10/38 (26%) pts SLN was positive, followed by radical surgery. In 3/28 ex tempore negative patients, histopathological analysis showed metastatic involvement (false negative). In 3/10 ex tempore positive patients micro metastases 0,2-2 mm were detected. 12 pts had 2 SLN, 8/12 (66%) had negative and 4/12 (34%) had positive SLN. 3 pts had a rare double drainage to axilla and a. mammaria int. Conclusion: Our results confirm that SLN detection technique is non-invasive, safe and reliable and should be incorporated into the guidelines for breast cancer pts (T1-2 N0 M0). The most reliable option for colloid application is the combined technique of periareolar and peritumoral injection. Patients with drainage to a. mammaria interna should be selected for adjuvant protocols.
Детекција на сентинелни лимфни Јазли кај карцином на дојка – први искуства